Acoustic and auditory phonetics - Johnson, Keith (Malden, Massachusetts : Blackwell Publishing, 2003)
Provides readers with an accessible yet rigorous introduction to phonetics and speech sciences. The first chapters introduce basic acoustics, audition, signal processing, and the acoustic theory of speech production. The book then surveys the major classes of sounds, describing them acoustically, auditorily, and perceptually. This second edition includes an new chapter on speech perception and additional selections on digital filtering and cross-linguistic vowel and consonant perception.
Includes bibliographical references (p. [169]-173) and index.
Keywords: Phonetics, Acoustic; Hearing; Phonétique acoustique